Soil fauna changing in after-pine harvesting's areas along a temporal gradient of Atlantic Forest regeneration - Casaril C.E.* (2024)
© 2024 Association of Applied Biologists.Monoculture of pine alters the soil fauna community structure, but forest farms, mixed with natural areas, are restoring the original vegetation to protect, the diversity and ecosystem functions. In restoration initiatives it is necessary to consider the soil fauna. Thus, the aim of this study was to investigate how the process of restoration of the soil community occurs over time in areas after pine harvesting. Areas in natural regeneration with 4 and 10 years, pine plantations adjacent to these areas (representing previous use), and areas of natural forest (reference) were evaluated, it was evaluated three areas per treatment, with six sampling points spaced 30 m apart, totalling 18 sampling points for each treatment (n = 18). Soil mesofauna and macrofauna were collected through soil monoliths and pitfall traps. The comparison of the statistical analysis was to check for changes in the soil fauna over time (4 and 10 years) compared with that observed in secondary forest areas. The study showed that, along the natural regeneration time (4 and 10 years), it was observed increments in the diversity and evenness of the soil community and a reduction in the dominance of groups like Formicidae and increases in the community structure complexity with the resurgence of micropredators/regulators (Collembola and Acari), litter transformers (Oligochaeta, Diplopoda, Blattodea, Coleoptera (Larva), Diptera (Larva) and Coleoptera) and predators (Pseudoscorpiones, Opiliones, Symphyla and Coleoptera) after 10 years of natural regeneration, the areas have already recovered groups with important ecosystem functions, but are not yet at the level of abundance, functional diversity and community structure of native forest areas. The 4- and 10-year regeneration areas present major number of soil fauna groups of native forest (20 groups in regeneration areas and 17 in the native forest areas). Even so, the forest showed a major complexity of soil fauna community structure, evidenced by the diversity. This study contributes to the understanding of natural regeneration for soil fauna along a temporal gradient and these findings can guide the conservation of regional soil fauna diversity.